Casa en Los Cardales (2007)
Material gráfico y memoria descriptiva de la casa en Los Cardales.
Keywords: VILA SEBASTIAN VILA & ASOCIADOS ARQUITECTOS; VILA, MARCELO; SEBASTIÁN, ADRIÁN; VILA, JAVIER; VIVIENDAS UNIFAMILIARES; VIVIENDAS RURALES; LOS CARDALES; BUENOS AIRES (PROV); ARGENTINA; CONSTRUCCION; BLOQUES DE HORMIGÓN; CUBIERTAS; CHAPA